Fatal Aspergillus fumigatus septicemia in a patient with an ectopic ACTH-producing neuroendocrine pancreatic tumor - Grobholz, Rainer; Back, Walter; Pörner, Tudor Constantin; Ertl, Georg; Bleyl, Uwe (Endocrine pathology, 1999)
The case of a 71-yr-old Caucasian patient who suffered from an adrenocorticotropic hormone (ACTH)-producing tumor and developed a fulminantAspergillus fumigatus septicemia is reported. The patient presented initially with a recent onset of hyperglycemia and had excessive plasma levels of cortisol and ACTH. A computer-assisted tomography scan showed a tumor associated within the head of the pancreas. During his hospital course, he developed a rapid progressive fatalAspergillus fumigatus pneumonia and an upper gastrointestinal bleeding. At necropsy multiple abscesses in the brain, lungs, heart, kidneys, small bowel and mesentery were present as a result of Aspergillus septicemia. A neuroendocrine pancreatic tumor, 8 cm in diameter, was found in the head of the pancreas without any signs of malignancy. The tumor showed immunohistochemical and electron microscopic evidence of ACTH expression, but of no other pituitary or pancreatic hormones. This case demonstrates the fulminant progress of a septicemia based on an immunologically compromised patient because of ectopic Cushing’s syndrome. Early diagnosis of ectopic ACTH syndromes is essential for adequate therapy in order to prevent complications and fatal infections.
Gesehen am 23.06.2022